2021
DOI: 10.1101/2021.03.24.436599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Herpesviral induction of germline transcription factor DUX4 is critical for viral gene expression

Abstract: DUX4 is a transcription factor and a master regulator of embryonic genome activation (EGA). During early embryogenesis, EGA is crucial for maternal to zygotic transition at the 8-cell stage in order to overcome silencing of genes and enable transcription from the zygotic genome. In adult somatic cells, DUX4 expression is largely silenced. Activation is likely pathogenic, and in adult muscle cells causes genetic disorder Facioscapulohumeral Muscular Dystrophy (FSHD). We identified activation of DUX4 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…In addition there are reports of DUX4 expression in human cancer. Interestingly, we and other could show, that DUX4 is induced by herpesviral infection (52)(53)(54). DUX4 is expressed upon lytic replication of herpesviruses by viral proteins, and knockout of DUX4 blocks replication of HSV-1 and HSV-2 almost completely.…”
Section: Herpesviruses and Pioneer Factorsmentioning
confidence: 70%
“…In addition there are reports of DUX4 expression in human cancer. Interestingly, we and other could show, that DUX4 is induced by herpesviral infection (52)(53)(54). DUX4 is expressed upon lytic replication of herpesviruses by viral proteins, and knockout of DUX4 blocks replication of HSV-1 and HSV-2 almost completely.…”
Section: Herpesviruses and Pioneer Factorsmentioning
confidence: 70%
“…We also suggest that herpesvirus is a relevant environmental modifier as we find that HSV-1 augments DUX4 production in SMCHD1 KO hESC and arhinia and FSHD2 iPSC more so than in WT hESC and control iPSC, respectively. HSV-1 may also induce DUX4 via a DNA damage response and p53 activity (48), although recent studies suggest a direct role for the viral immediate early proteins ICP0 and ICP4 in DUX4 up-regulation (49). HSV-1 is a common sexually transmitted disease among women of reproductive age, and it can, in rare circumstances, be transmitted to the fetus during pregnancy with severe consequences (e.g., microcephaly and fetal demise) (50).…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that the germline transcription factor DUX4 is expressed in the context of DNA virus infection, namely herpesviruses (HSV-1, HSV-2, HCMV, KSHV and EBV), papillomaviruses (HPV16) and polyomaviruses (MCPyV) (51). Along this line, we wanted to investigate whether herpesviral infections also induce TEs expression in vivo.…”
Section: Tes Are Upregulated In Dna Virus Associated Human Cancersmentioning
confidence: 99%
“…The raw sequencing datasets have been uploaded to the Gene Expression Omnibus (GEO) database, including RNA-Seq of DUX4 over-expression (GSE253543) and RNA-Seq of HCMV infection and KAP1 knockdown (GSE256111). The study used publicly available datasets from GEO, including bulk RNA-seq of HSV-1 infection (GSE59717) (61), ATAC-seq of HSV-1 infection (GSE100611) (62), CHIP-seq of H3K9me3 and H3K27me3 upon HSV-1 infection (GSE124803) (47), CHIP-seq of KAP1 (GSE72622) (63), RNA-seq of DUX4-KO (GSE234489) (51), CHIP-seq of DUX4 (GSM837613 and GSE174759) (64)(51), as well as the single-cell RNA-seq data of nasopharyngeal carcinoma (GSE162025) (65), Head and neck squamous cell carcinoma (GSE164690) (66) and Merkel cell carcinoma tumor (GSE226438) (67). UCSC genome browser session links for the ATAC-seq.…”
Section: Data Availabilitymentioning
confidence: 99%